Age related vascular endothelial function following lifelong sedentariness: positive impact of cardiovascular conditioning without further improvement following low frequency high intensity interval training. Issue 1 (27th January 2015) - Grace, Fergal M.; Herbert, Peter; Ratcliffe, John W.; New, Karl J.; Baker, Julien S.; Sculthorpe, Nicholas F.
Abstract: Aging is associated with diffuse impairments in vascular endothelial function and traditional aerobic exercise is known to ameliorate these changes. High intensity interval training (HIIT) is effective at improving vascular function in aging men with existing disease, but its effectiveness remains to be demonstrated in otherwise healthy sedentary aging. However, the frequency of commonly used HIIT protocols may be poorly tolerated in older cohorts. Therefore, the present study investigated the effectiveness of lower frequency HIIT (L f HIIT) on vascular function in a cohort of lifelong sedentary (SED; n  =   22, age 62.7 ± 5.2 years) men compared with a positive control group of lifelong exercisers (LEX; n  = 17, age 61.1 ± 5.4 years). The study consisted of three assessment phases; enrolment to the study (Phase A), following 6 weeks of conditioning exercise in SED (Phase B) and following 6 weeks of low frequency HIIT in both SED and LEX (L f HIIT; Phase C). Conditioning exercise improved FMD in SED (3.4 ± 1.5% to 4.9 ± 1.1%; P  <   0.01) such that the difference between groups on enrolment (3.4 ± 1.5% vs. 5.3 ± 1.4%; P  <   0.01) was abrogated. This was maintained but not further improved following L f HIIT in SED whilst FMD remained unaffected by L f HIIT in LEX. In conclusion, L f HIIT is effective at maintaining improvements in vascular function achieved during conditioning exercise in SED. L f HIIT is a well‐tolerated and effective exercise mode for reducing cardiovascular risk and maintaining but does not improve vascular function beyond that achieved by conditioning exercise in aging men, irrespective of fitness level. Abstract : e12234 The effects of low frequency high intensity interval training (HIIT) on vascular endothelial function in lifelong sedentary men remains currently unknown. The present study examined the impact of low frequency HIIT following conditioning exercise on low determinants of vascular endothelial function and angiogenic biomarkers in aging men compared with a positive control group of similarly aged. The major findings of this study indicate that low frequency HIIT is a well‐tolerated and effective exercise mode for reducing cardiovascular risk and maintaining but not improving endothelial function beyond that achieved by conditioning exercise in aging men, irrespective of fitness level.